Accuracy in orthognathic surgery─comparison of preoperative plan and postoperative outcome using computer-assisted two-dimensional cephalometry by the Onyx Ceph® system. Issue 10 (October 2018) - Legal, Stefan; Moralis, Antonios; Waiss, Waltraud; Zeman, Florian; Winkler, Cornelia; Müller, Steffen; Reichert, Torsten E.; Proff, Peter; Meier, Johannes; Klingelhöffer, Christoph; Gosau, Martin; Ettl, Tobias
Abstract: Purpose: This retrospective study analyzes deviations between preoperative planning and postoperative outcome in orthognathic surgery using 2D Onyx Ceph ® -cephalometric analyzing and planning system. Materials and methods: A total of 100 patients with a mean age 25.1 of years were included in this study. In 33 patients a bilateral sagittal split osteotomy and in seven patients a Le Fort I osteotomy was performed. A total of 60 patients were treated by a bimaxillary approach. Onyx Ceph ® was used as cephalometric planning software (Onyx Ceph ® ), followed by mock operations. Postoperative cephalograms were obtained after 3.3 days and compared to preoperative planning cephalograms for sagittal (SNA, SNB, ANB) and vertical (ArGoMe, ML-NSL, NL-NSL) angle measurements. Real and absolute mean deviation were documented. Results: Absolute mean deviation (degrees) between postoperative and planned jaw movement was lower for the sagittal parameters SNA (0.58), SNB (1.15) and ANB (1.05) compared to the vertical parameters NL-NSL (1.47), ML-NSL (1.96) and ArGoMe (3.20). SNA, SNB and ANB showed constant deviations independent from the extent of jaw movement. With regard to the vertical parameters ML-NSL, ArGoMe and NL-NSL the extent of the postoperative rotational jaw movement was not as much as planned, particularly for vertical shifts of more than 4°. Conclusion: By using the 2D Onyx Ceph ® cephalometric software for orthognathic surgery, the deviations between planned and actual movements are within an acceptable and predictable range. Planning of extensive vertical alterations may result in greater deviations after surgery.